A Non‐Gradient Model of Turbulent Gas Fluxes Over Land Surfaces. Issue 14 (19th July 2021) - Tang, Y.; Shahnaz, S.; Wang, J.
Abstract: A non‐gradient model is formulated for estimating gas fluxes using single‐level time‐series data of near‐surface gas concentration over land surfaces. When the vertical turbulent transport process in the atmospheric surface layer is described by a one‐dimensional diffusion equation, a gas flux is expressed as a weighted integral of the time‐history of single‐level gas concentration. The eddy‐diffusivity may be parameterized as a function of sensible heat flux based on the Monin‐Obukhov similarity theory without explicit dependence on wind speed and surface roughness. Sensible heat flux may be estimated from net radiation and surface temperature using the maximum entropy production model. Case studies at six sites with diverse vegetation covers, geographic and climatic conditions at sub‐daily and seasonal scales demonstrate the model's capability of simulating water vapor and CO2 fluxes using fewer inputs than other models. The proposed method provides an alternative modeling tool for the study of water and carbon cycles over vegetated land surfaces. Plain Language Summary: We develop a non‐gradient model of gas fluxes in the atmospheric surface layer. The model accurately estimates water vapor and CO2 fluxes at field sites with diverse climatic and vegetation conditions at diurnal and seasonal scales. The model can be used to study water and carbon cycles over vegetated land surfaces. Key Points: Gas fluxes derived from single‐level gas concentration data without using concentration gradient, wind speed, or surface roughness data A new parameterization of eddy diffusivity based on the extremum solution of Monin‐Obukhov similarity theory Estimation of water vapor and CO2 fluxes under contrasting climate and vegetation conditions at diurnal and seasonal scales